ANALISIS KUALITAS SOAL PILIHAN GANDA MELALUI SIMULASI TUGAS PROYEK PADA MAHASISWA PENDIDIKAN EKONOMI MENGGUNAKAN SPSS - Epelima Sinaga; Mizael Demak Sitohang; Emia Perangin Angin; Agnes Dea Lita Br Sitepu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of the quality of evaluation instruments in accurately measuring students’ abilities, particularly multiple-choice items developed by students through project-based assignments. However, the instruments produced often have not undergone a comprehensive item analysis, so their validity and reliability cannot be assured. This study aims to analyze the quality of multiple-choice test items constructed by Economics Education students through a project-based simulation using the SPSS application. The method employed is a quantitative approach with a descriptive research design. The subjects of this study consisted of 35 students, while the research object comprised 20 test items on the topic of market failure. Data were collected through an online instrument trial and analyzed using tests of validity, reliability, difficulty level, discrimination index, and distractor effectiveness. The results showed that 75% of the items were valid and 25% were invalid. The reliability coefficient of 0.802 indicates a high category. The level of difficulty was dominated by easy items (80%) and moderate items (20%), with no difficult items identified. The discrimination index was mostly categorized as very good (65%), although some items were still in the fair and poor categories. The effectiveness of distractors varied, with some distractors not functioning optimally. Therefore, in general, the quality of the test items can be considered good; however, revisions are still needed to improve the balance of difficulty levels and the effectiveness of distractors.